(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The following paper deals with the comparison of adhesion of specimens made of fired clay and selected adhesives. The adhesion was tested on specimens at the age of one, two and three days in order to determine the parameters of young masonry. Nine different adhesives (adhesives intended for masonry and adhesives for others material) were tested in total. The above mentioned test is not standardized. The obtained results from the adhesion test determine the tensile strength between the adhesive and the fired clay and the adhesion of selected adhesive to the fired clay. The small specimens were made of two ceramic plates and an adhesive. Selected adhesives were applied to ceramic plates according to the usual standards. Eighty-one small specimens were produced in total – twenty-seven specimens for the adhesion test at each defined age of the specimens (one day, two days, three days). The produced specimens were cured in the climatic chamber with set laboratory conditions until the time of the test. The specimens were tested in the laboratory of the Heluz brick plant in Dolní Bukovsko. This paper deals with the procedure of preparation of the specimens, the course of the test and the comparison of gained results.